2020
DOI: 10.3390/jcm9010131
|View full text |Cite
|
Sign up to set email alerts
|

The Present Utility of the Oxytocin Challenge Test—A Single-Center Study

Abstract: Introduction: The oxytocin challenge test (OCT) used to be one of the most important tools in assessing fetal well-being before ultrasonography became prevalent. We show that, after modifying the classification of the results and the intervention algorithm, OCT can still be a useful tool in present-day obstetrics. Material and methods: The study included 318 OCTs performed in patients admitted to our department from 2010 to 2012. A modified classification of test results was introduced, dividing the results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…In the study of Waledziak et al, 69 (33.8%) of 204 patients with negative OCT underwent C/S. The authors found that abnormal heart traces comprised 37.6% of C/S indications [10]. The C/S rate in our study was in agreement with study as mentioned above.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study of Waledziak et al, 69 (33.8%) of 204 patients with negative OCT underwent C/S. The authors found that abnormal heart traces comprised 37.6% of C/S indications [10]. The C/S rate in our study was in agreement with study as mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…OCT is a test used to evaluate fetal well-being based on uterine contractions in suspected placental insu ciency. The negative OCT test was de ned as the presence of accelerations in fetal heart rate, normal variability, and absence of slowdown in uterine contractions [10]. Freeman et al used the CST for follow-up in 679 post-term cases and observed no perinatal mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, another group of researchers have reported much less (40%) rate of fetal heart rate abnormalities associated with oxytocin use. The rate, though less than what we found, is considerable 14 .…”
Section: Discussioncontrasting
confidence: 74%
“…Colorful ultrasound examination showed that the anterior and posterior diameter of uterus was significantly larger than the normal value [ 33 ]. The key point for the prevention and treatment of postpartum uterine involution is how to promote postpartum uterine contraction, reduce postpartum hemorrhage, and reduce lochia time [ 34 – 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key point for the prevention and treatment of postpartum uterine involution is how to promote postpartum uterine contraction, reduce postpartum hemorrhage, and reduce lochia time [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%